2020
DOI: 10.1093/cid/ciaa1474
|View full text |Cite
|
Sign up to set email alerts
|

Emerging RNA-Dependent RNA Polymerase Mutation in a Remdesivir-Treated B-cell Immunodeficient Patient With Protracted Coronavirus Disease 2019

Abstract: SARS-CoV-2 is a new pandemic virus for which Remdesivir is the only antiviral available. We report the occurrence of a mutation in the RdRP (D484Y) following failure of remdesivir in a 76-year-old woman with a post-rituximab B-cell immunodeficiency and persistent SARS-CoV-2 viremia. Cure was reached after supplementation with convalescent plasma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
95
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(100 citation statements)
references
References 9 publications
4
95
1
Order By: Relevance
“…Patient sequences all belonged to clade 20B, corresponding to lineage B.1.1. According to literature data, [18][19][20][21][22][23][24][25] no mutations related to possible resistance to remdesivir were observed, also as minority variant when considering a cut off of 1%.…”
Section: Case Historymentioning
confidence: 97%
“…Patient sequences all belonged to clade 20B, corresponding to lineage B.1.1. According to literature data, [18][19][20][21][22][23][24][25] no mutations related to possible resistance to remdesivir were observed, also as minority variant when considering a cut off of 1%.…”
Section: Case Historymentioning
confidence: 97%
“…However, with the increased mutation rate of SARS-CoV-2, the susceptibility of the virus to remdesivir drugs has been challenged. In addition, there are certain cases across 30 different countries associated with the failure of this antiviral agent (Martinot et al 2020). Therefore, until the availability of specific treatment against COVID-19, prevention is the only measure.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have shown that naturally emerging mutations in RdRp may lead to drug resistance or reduce treatment efficacy due to weakened drug-RdRp binding, particularly near the mutation sites [35] , [107] , [108] , [109] . In a recently published case report, a point mutation in RdRp (D484Y) was associated with the failure of remdesivir treatment in a 76-year-old female COVID-19 patient with post-rituximab B-cell immunodeficiency [110] . It is suspected that resistant mutations emerge under remdesivir treatment pressure which leads to treatment failure [110] .…”
Section: The Impact Of Mutations On Drug Safety and Efficacymentioning
confidence: 97%
“…In a recently published case report, a point mutation in RdRp (D484Y) was associated with the failure of remdesivir treatment in a 76-year-old female COVID-19 patient with post-rituximab B-cell immunodeficiency [110] . It is suspected that resistant mutations emerge under remdesivir treatment pressure which leads to treatment failure [110] . Therefore, it is crucial to identify resistant mutations and evaluate their impact on the conformation and activity of RdRp and its susceptibility to antiviral treatment.…”
Section: The Impact Of Mutations On Drug Safety and Efficacymentioning
confidence: 97%